(untitled) - Evans, G. Edward (Westport, Conn., 2005)
This book covers all phases of collection development--from needs assessment, policies, and the selection process (theory and practice), to publishers, serials, protection, legal issues, censorship, and intellectual freedom. Each chapter has been extensively revised to reflect changing practices, policies, and technologies. To this end, some chapters--electronic materials, government information, audiovisual materials, and resource sharing--have been almost completely rewritten. In addition, electronic serials, introduced in the 4th edition, has been combined with its print counterpart in a single chapter. New to this edition is a CD containing supplementary material; a companion Web site will also be maintained to ensure URLs referenced throughout the text are kept up to date
Keywords: Phát triển vốn tài liệu (thư viện),Collection development (Libraries),Information services,Dịch vụ thông tin; Hoa Kỳ,United States,United States,Hoa kỳ